Cardiomyopathy and Frequent Monomorphic PVC : Which One Comes First? - Anita Surya Santoso; Djanggan Sargowo; Ardian Rizal (Universitas Brawijaya, 2022)
A 28-year-old male wasaadmittedto hospitalwwith chief complaint chestadiscomfort. There were symptoms of dyspnea on effort and palpitation before. He had a history of alcoholics for more than five years. The ECG showed frequent Premature Ventricular Complex (PVC) and recommended to have ambulatory Holter monitoring with conclusion frequent monomorphic right ventricle outflow tract (RVOT) origin PVC. Echocardiography indicated a decrease in left ventricular (LV) function, LV dilatation, and global hypokinetic. Cardiac Magnetic Resonance Imaging (CMR) was performed, and there was no “edema”and myocardium fibrosis. It is essential to analyze which comes first, arrhythmia induced cardiomyopathy (AIC), or cardiomyopathy induced arrhythmia to have direct treatment. From the collected data, we conclude that the frequent RVOT origin PVC induced cardiomyopathy and catheter ablation is the definitive therapy.